Characterization and evaluation of Indian multivoltine silkworm (Bombyx mort) germplasm - MUKHERJEE, S; MUKHERJEE, P; SAHANI, N K; SINHA, R K (The Indian Journal of Agricultural Sciences, 2013)
Variability, heritability, genetic gain as per cent of mean and correlations were studied for 9 quantitative characters among 56 muitivoltine silkworm (Bombyx mori L.) breeds. Wide variability was recorded among the breeds for morphological and quantitative characters. Fecundity, weight of mature larvae, fifth instar’ larval duration, yield/1O 000 larvae by weight, cocoon weight and shell weight showed high genotypic coefficient of variation (gcv), heritability and genetic advance as per cent of mean, indicating possibility of further improvement through selection. The correlation of yield/1O 000 larvae by weight with cocoon weight, shell weight and shell ratio (%) was significant and positive, whereas yield/1O 000 larvae by number did not show association with any of the characters except yield/10 000 larvae by weight. Similarly, total larval dumtion was positively correlated with fifth instar larval duration, but both these variables were not associated with any other characters. The study revealed that one set of variables may control the expression of other set of characters. The breeds like ’MHMP (Y)’, ’A 13’, ’Hosa Mysore’, ’AP 12’ and ’MW 13’ could be identified potential genotypes for the improvement of multivoltine silkworm through appropriate breeding programme.